Venetoclax combined chemotherapy versus chemotherapy alone for acute myeloid leukemia: a systematic review and meta-analysis - Zhu, Jingkui; Fan, Jixin; Xie, Tiantian; Zhao, Haiqiu; Lu, Runqing; Zhang, Yinyin; Li, Yingmei; Xie, Xinsheng; Wan, Dingming; Jiang, Zhongxing; He, Fei; Guo, Rong (Frontiers in Oncology, 2024)
Objective: To compare the efficacy and safety of venetoclax (VEN) in combination with chemotherapy (chemo) versus chemo alone in the treatment of acute myeloid leukemia (AML). Method: To compare the efficacy and/or safety of VEN+chemo versus chemotherapy alone for AML, PubMed, Embase, Web of Science, and the Cochrane Library were used to searching up to June 2023. Comparisons included complete remission (CR), CR with incomplete hematologic recovery (CRi), morphologic leukemia-free state (MLFS), overall response rate (ORR), and adverse events (AEs). Result: A total of 9 articles were included, including 3124 patients. The baseline characteristics between two patient groups were similar. The combined analysis showed that compared with the group receiving chemo alone, the VEN+chemo group exhibited higher rates of CR, CRi, MLFS and ORR. Additionally, the VEN+chemo group had longer event-free survival (EFS) and overall survival (OS) durations. The incidence rates of AEs and serious AEs (SAEs) were similar between the two groups, but the early 30-day mortality rate was lower in the VEN+chemo group than in the chemo alone group. Conclusion: The VEN+chemo therapy demonstrates significant efficacy and safety profile in AML patients. However, more prospective studies are needed in the future to provide more accurate and robust evidence for treatment selection in patients.